Sensitivity Enhancement of Heterocore Macrobend Fiber Optics by Adding a ZnO Film - Mohd Arif, Noor Azie Azura; Berhanuddin, Dilla Duryha; Ehsan, Abang Annuar (International Journal of Optics, 2021)
Optical fibers with high sensitivity are in demand due to their great potential in sensor application. Semiconductors, such as ZnO, are good materials. Using them as a second cladding offers opportunities in realizing next-generation multimaterial fiber optics. COMSOL Multiphysics is used to simulate heterocore macrobend fiber optics with the same curvature radius but different values of refractive index and thickness of ZnO films. The optimum thickness of ZnO films is identified by determining the loss of optical fibers. Macrobend heterocore fiber optics by adding ZnO thin film has been established by simulating and interpreting the relationship in terms of transmission and refractive index in the evanescent field. These results will provide a reliable fundamental to guide the performance in practice.